Comparison of Money Laundering Criminal Law Between Indonesia and Malaysia - Widijowati, Dijan; Cartin Pecson, Rowela (Greenation Research & Yayasan Global Resarch National, 2023)
One form of crime that has become a primary focus of criminal efforts is money laundering. The process of improvement continues to evolve until today, with recent changes outlined in Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering. In addition to the national scale, efforts to combat money laundering are also carried out internationally. A significant step in international cooperation to combat money laundering is the establishment of the Financial Action Task Force (FATF) on Money Laundering. However, despite these collective efforts, there are still several challenges and obstacles in preventing money laundering globally. Differences in laws and regulations between countries, as well as the complexity of global financial pathways, are some factors that complicate the eradication efforts. Therefore, this research will focus on examining how the regulation of money laundering crimes differs between Indonesia and Malaysia and how the regulations compare in both countries. Specifically, this normative legal research generally focuses on the analysis of legal documents. The formulated issues can be outlined as follows: How is the regulation of money laundering crimes in Indonesia and Malaysia, and what is the comparison of the regulations on money laundering crimes in Indonesia and Malaysia.